MENINGKATKAN KEMAMPUAN MENYIMAK MELALUI METODE BERCERITA DENGAN BONEKA JARI PADA ANAK USIA 4-5 TAHUN DI KB AL-ABRAR DESA TEBERAU PANJANG KECAMATAN GUNUNG TOAR. - Yumparida '; Mahdum '; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observations on listening skills through storytelling with finger puppets in children aged 4-5 years is still low and teachers are still using methods that dominate and not varied. The problems that arise in the listening skills of children aged 4-5 years play group Al-Abrar Teberau Panjang. This study aims to determine the increase listening skills through storytelling with finger puppets in children aged 4-5 years in a play group Al-Abrar Teberau Panjang district Gunung Toar. The sample used in this study amounted to 15 childrens. Based on data analysis and the results showed that percentage of listening skills through storytelling with finger puppets increase significantly. Can be seen from the results of prior actions is 39.2% and then perform an action using a finger puppet, subsequently implemented the results obtained 41.62% next actions result 74.4%. If seen before by the actions that are in the low category as many as 12 children or 80%, moderate category as many as 3 children or 20% and there is no higher category or 0%. It can be seen that after the treatment, the listening skills of children has increased very significantly that there are children who are in the high category as many as 5 children or 33.33%, moderate category as many as 10 people or 66.34%, and there is no children in the low category or 0%.